Community Resistance Movement Against Mining: Case Study of the Save Sangihe Ikekendage (SSI) Movement Against PT. Tambang Mas Sangihe (TMS) in the Gold Mining Case in Sangihe Islands Regency, North Sulawesi Province for the 2020-2024 Period - Maarif, Agus; Mar'iyah, Chusnul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study examines the Save Sangihe Island (SSI) movement against PT. Tambang Mas Sangihe (TMS) in 2020-2024 in the case of gold mining in the Sangihe Islands Regency, North Sulawesi. The study uses the theory of contentious politics to explain the resistance of the movement. The research method uses a qualitative method to explore the social phenomenon of the SSI movement against PT. TMS by asking a number of in-depth research questions. The results of the study show that the SSI movement emerged as a response to ecological threats and violations of the right to living space due to mining policies in small island areas that should be legally protected. By using a qualitative approach and a contentious politics framework, this study analyzes how SSI builds resistance through the mobilization of social resources, elite support, litigation, collective action repertoires, and framing of resistance narratives. The findings show that SSI's success lies not only in the strength of the masses, but also in the effectiveness of strategic networks, moral legitimacy, and adaptive abilities in the face of state repression. This study contributes to strengthening the theory of contentious politics by emphasizing the importance of the interaction between political opportunities, resistance tactics, and symbolic power in fighting PT. TMS which has strong resources.